Bahasa Tidak Resmi di Media Sosial: Analisis Komentar Netizen di Instagram Pusdatin Kemendikbudristek - Syamsi, Nur (GERAM, 2024)
This research focuses on the use of unofficial language used by netizens in the comment column, especially on the official account of the Ministry of Education and Culture. The use of unofficial language is feared to cause misunderstandings and affect the fading of concern for the good and correct Indonesian language. This study aims to examine the unofficial language in the comment column on the Instagram pusdatin of the Ministry of Education and Culture as an official account. The research carried out is a literature research, namely by making netizens' comments on the Instagram account of the Ministry of Education and Culture as study material. The data was collected and then reduced and displayed according to groups and then analyzed descriptively. The findings obtained are that there are 20 unofficial languages with details of 8 abbreviations, 6 slang and 6 foreign languages. The results of this research can be used as educational material for netizens so that they can understand that official and unofficial communication also applies on social media, netizens can find out non-standard language that should be avoided when commenting on the official accounts of state institutions, especially the Ministry of Education and Buristek's pusdadin. In general, these findings can provide insight to readers to try to adjust the situation to the right choice of words in communicating on social media.